ANALISIS RASIO EFEKTIFTAS KEUANGAN PADA DINAS PENDAPATAN DAERAH (DISPENDA) KOTA MAKASSAR - Ester Tamallo (AkMen JURNAL ILMIAH, 2011)
The purpose of this study To determine the effectiveness ratio of Finance at the Department of Revenue (Revenue) Makssar city if it is effective. The research method used in this study is "quantitative methods" of effectiveness ratio analysis. The results of the research is the area of the Autonomous City of Makassar, there are still some parts of the Revenue is less effective when measured by the ratio of regional financial effectiveness (EKD), which ranges from> 39.12 to 77.55%. However, when viewed in terms of implementation of financial management of the city of Makassar participatory pattern. Revenue in 2008, compared to the revenue base year 2005, the trend of the financial effectiveness of the autonomous regions Makassar city increased, except in some parts such as, other local revenues, fund balance rather than taxes.